2007
DOI: 10.2175/106143007x156826
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factor Activity Relationships: Challenges and Development Approaches

Abstract: Virulence factor activity relationships (VFAR) is a predictive approach proposed by the National Research Council's Committee on Drinking Water Contaminants (Washington, D.C.) to classify and rank waterborne pathogens. It is based on the presumption that health threats of waterborne pathogens can be predicted from descriptors at different levels of cellular organization. This paper summarizes challenges that need to be addressed while developing VFAR, with a focus on genomics, such as genomic variability among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Sequence variability of a virulence gene in various pathogens poses a great challenge for the development of real-time PCR and biochip assays to be used for accurate identification and quantification of pathogens in environmental samples (Tourlousse et al 2007). In this study, we observed high Ct values when using Aeromonas isolates to validate the developed real-time PCR assays.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Sequence variability of a virulence gene in various pathogens poses a great challenge for the development of real-time PCR and biochip assays to be used for accurate identification and quantification of pathogens in environmental samples (Tourlousse et al 2007). In this study, we observed high Ct values when using Aeromonas isolates to validate the developed real-time PCR assays.…”
Section: Discussionmentioning
confidence: 68%
“…The National Research Council's Committee on Drinking Water Contaminants (Washington, DC) has recommended a comprehensive approach based on the virulence factor activity relationships as a means to predict potential risks from a wide range of pathogens in drinking water. The needs to know better about the distribution and genetic level of virulence genes of waterborne pathogens are supported by many previous studies (Tourlousse et al 2007;Miller et al 2008). These studies have suggested that relying on only one single virulence gene of pathogenic strains might possibly lead to incorrect assessment of the microbial risk of waterborne diseases because (1) many virulence genes are unevenly distributed among different pathogenic strains, (2) many virulence genes are multifunctional, and (3) some virulence can be even found in nonpathogenic strains.…”
Section: Introductionmentioning
confidence: 95%
“…[140][141][142][143][144][145] An even greater challenge lies in the extension of QSAR methods to biological properties like virulence (i.e., virulence factor activity relationships, VFARs). [146][147][148] The challenges involved in implementing useful VFARs are considerable, but may eventually succumb to the combination of advances from computational toxicology 1 and omic sciences. 149…”
Section: Future Prospectsmentioning
confidence: 99%
“…More often, these developments are based on studies that predate the first VFAR report and do not necessarily use the term – VFAR. In fact, of the more than one hundred publications reviewed here due to their relevance to VFARs, only few 58 refer to the original National Research Council report. 1 This exemplifies that the need for developing the ability to predict functions including virulence based on sequence information is universal and includes scientists engaged in predicting increased risk of infectious diseases due to climate change, clinicians engaged in predicting antimicrobial resistance, and regulatory bodies engaged in ensuring public and ecosystem health, among many others.…”
Section: Introductionmentioning
confidence: 99%